2019
DOI: 10.1098/rsif.2019.0108
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of different orthodontic loading on root resorption and correlation with mechanobiological stimulus in periodontal ligament

Abstract: Orthodontic root resorption is a common side effect of orthodontic therapy. It has been shown that high hydrostatic pressure in the periodontal ligament (PDL) generated by orthodontic forces will trigger recruitment of odontoclasts, leaving resorption craters on root surfaces. The patterns of resorption craters are the traces of odontoclast activity. This study aimed to investigate resorptive patterns by: (i) quantifying spatial root resorption under two different levels of in vivo orthodontic loadings using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
101
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(115 citation statements)
references
References 55 publications
12
101
1
1
Order By: Relevance
“…Compared between the two different sliding mechanics, we could clearly find that the pressure stresses on teeth and periodontal tissue in miniscrew sliding mechanics was lower than in intramaxillary retraction. The research from Zhong et al stated heavy pressure in PDL generated by orthodontic forces lead to larger root resorption volumes than light pressure [23]. These results indicated that a long power arm combined with miniscrews could produce even pressure on PDL during retraction, which were expected in clinical treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Compared between the two different sliding mechanics, we could clearly find that the pressure stresses on teeth and periodontal tissue in miniscrew sliding mechanics was lower than in intramaxillary retraction. The research from Zhong et al stated heavy pressure in PDL generated by orthodontic forces lead to larger root resorption volumes than light pressure [23]. These results indicated that a long power arm combined with miniscrews could produce even pressure on PDL during retraction, which were expected in clinical treatment.…”
Section: Discussionmentioning
confidence: 97%
“…The extent of the resorption also depends on the amount of force and torque applied [61][62][63]. In a recent study, no clear resorption was found in the traction region, which can suggest that odontoclasts do not respond to traction stimuli [64]. The pressure exerted by the tooth root on the bone and the surrounding PDL is the main factor determining the rate of tooth movement, not the force exerted on the tooth crown [65].…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive orthodontic treatment and heavy forces may induce root resorption [ 24 , 25 ]. The heavier the forces applied, the larger the total root resorption volume, as shown by microCT imaging techniques [ 26 ]. The treatment plan and the biomechanics selected for this patient aimed to avoid root resorption: entity of tooth forces was kept to low levels, a custom made trans-palatal arch was used for the traction of the canines and only round archwires/light forces were applied.…”
Section: Discussionmentioning
confidence: 99%